Reporting of environmental outcomes in randomised clinical trials : a protocol for a scoping review - Petersen, Johanne Juul; Hemberg, Linn ; 0000-0002-0557-878X; Thabane, Lehana; Hopewell, Sally; Chan, An Wen; Hróbjartsson, Asbjørn; Mathiesen, Ole; Kandasamy, Sujane; Siegfried, Nandi; Williamson, Paula R.; Fox, Lisa; Kamp, Caroline Barkholt; et al. (BMJ Open, 2025)
Introduction: To increase the sustainability of healthcare, clinical trials must assess the environmental impact of interventions alongside clinical outcomes. This should be guided by Standard Protocol Items: Recommendations for Interventional Trials (SPIRIT) and Consolidated Standards of Reporting Trials (CONSORT) extensions, which will be developed by The Implementing Climate and Environmental Outcomes in Trials Group. The objective of the scoping review is to describe the existing methods for reporting and measuring environmental outcomes in randomised trials. The results will be used to inform the future development of the SPIRIT and CONSORT extensions on environmental outcomes (SPIRIT-ICE and CONSORT-ICE). Methods and analysis: This protocol outlines the methodology for a scoping review, which will be conducted in two distinct sections: (1) identifying any existing guidelines, reviews or methodological studies describing environmental impacts of interventions and (2) identifying how environmental outcomes are reported in randomised trial protocols and trial results. A search specialist will search major medical databases, reference lists of trial publications and clinical trial registries to identify relevant publications. Data from the included studies will be extracted independently by two review authors. Based on the results, a preliminary list of items for the SPIRIT and CONSORT extensions will be developed. Ethics and dissemination: This study does not include any human participants, and ethics approval is not required according to the Declaration of Helsinki. The findings from the scoping review will be published in international peer-reviewed journals, and the findings will be used to inform the design of a Delphi survey of relevant stakeholders. Open science: Registered with Open Science 28 of February 2025.
Keywords: Climate Change; PUBLIC HEALTH; STATISTICS & RESEARCH METHODS